A clean conversion of aldehydes to nitriles using a solid-supported hydrazine - Baxendale, IR; Ley, SV; Sneddon, HF (Synlett: Accounts and Rapid Communications in Synthetic Organic Chemistry, 2002)
A polymer-supported hydrazine reagent has been applied to the conversion of a range of aldehydes to nitriles, providing a clean and efficient route to more diverse building blocks for combinatorial chemistry programmes.
Estimated acceptance date